Laser‐Induced Graphene in Controlled Atmospheres: From Superhydrophilic to Superhydrophobic Surfaces. Issue 27 (12th May 2017) - Li, Yilun; Luong, Duy Xuan; Zhang, Jibo; Tarkunde, Yash R.; Kittrell, Carter; Sargunaraj, Franklin; Ji, Yongsung; Arnusch, Christopher J.; Tour, James M.
Abstract : The modification of graphene‐based materials is an important topic in the field of materials research. This study aims to expand the range of properties for laser‐induced graphene (LIG), specifically to tune the hydrophobicity and hydrophilicity of the LIG surfaces. While LIG is normally prepared in the air, here, using selected gas atmospheres, a large change in the water contact angle on the as‐prepared LIG surfaces has been observed, from 0° (superhydrophilic) when using O2 or air, to >150° (superhydrophobic) when using Ar or H2 . Characterization of the newly derived surfaces shows that the different wetting properties are due to the surface morphology and chemical composition of the LIG. Applications of the superhydrophobic LIG are shown in oil/water separation as well as anti‐icing surfaces, while the versatility of the controlled atmosphere chamber fabrication method is demonstrated through the improved microsupercapacitor performance generated from LIG films prepared in an O2 atmosphere. Abstract : The modification of graphene‐based materials has been an important topic, and this study aims to expand the properties of laser‐induced graphene (LIG). With a controlled atmosphere chamber, both superhydrophobic and superhydrophilic LIG surfaces can be obtained. Characterizations show that the different wetting properties result from surface morphology and chemical composition. Applications are demonstrated in oil/water separation, anti‐icing, as well as micro‐supercapacitors.